Fundamentals of telemedicine and telehealth - Gogia, Shashi; Novaes, Magdala; Basu, Arindam; Gogia, Kriti; Gogia, Spriha (Academic Press, 2020)
Fundamentals of Telemedicine and Telehealth provides an overview on the use of information and communication technologies (ICTs) to solve health problems, especially for people living in remote and underserviced areas. With the advent of new technologies and improvement of internet connectivity, telehealth has become a new subject requiring a new understanding of IT devices and how to utilize them to fulfill health needs. The book discusses topics such as digitizing patient information, technology requirements, existing resources, planning for telehealth projects, and primary care and specialized applications. Additionally, it discusses the use of telemedicine for patient empowerment and telecare in remote locations. Authored by IMIA Telehealth working group, this book is a valuable source for graduate students, healthcare workers, researchers and clinicians interested in using telehealth as part of their practice or research. Presents components of healthcare that can be benefitted from remote access and when to rely on them. Explains the current technologies and tools and how to put them to effective use in daily healthcare. Provides legal provisions for telehealth implementation, discussing the risks of remote healthcare provision and cross border care.